CORPORATE ENTREPRENEURSHIP AND FIRM PERFORMANCE: EVIDENCE FROM SELECTED SMES IN SOUTH-WEST, NIGERIA - Ayorinde, Afisat Abolore; Yusuf, Dayang Hasliza Muhd; Ghani, Mohd Rosli Abdul; Jamaluddin, Raziff; Kamaruddin , Nur Syuhadah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Small and Medium Enterprises (SMEs) are globally recognised as key drivers of economic development. Considering their significant contribution to nation building, researchers have considered corporate entrepreneurship as a strategy that facilitates their effort in exploiting their present competitive advantages and exploring new business opportunities for performance improvement. Nevertheless, research on corporate entrepreneurship and SMEs has mainly focused on large firms or multinational enterprises in the context of developed countries, with sparse studies in developing countries. Thus, this study aims at filling this gap and draws on dynamic capabilities theory to investigate the effect of corporate entrepreneurship on firm performance of SMEs in Nigeria, being one of the developing countries of the world. To achieve this aim, probability sampling of stratified, proportionate, and simple random technique was employed to collect data from 445 owner managers/CEOs via a pre-tested structured questionnaire. The selected SMEs include; manufacturing, wholesale/retail trade, and education sectors operating in Lagos, Oyo, and Ogun states in the South-West geopolitical zone of Nigeria. Statistical package for social science (SPSS) software Version 30 was used for the analysis of demographic characteristics of the respondents and firms and partial least squares structural equation modeling (PLS-SEM) SmartPLS 4 software was utilized for the analysis of inner model and outer model. The results show that all the hypothesised relationship are supported. Innovation has the highest effect on the performance of the studied SMEs, followed by strategic renewal and corporate venturing. The present study contributes to the existing literature on corporate entrepreneurship and performance of SMEs through empirical evidence.